Terrigenous particles regulate autotrophic and heterotrophic microbial assembly and induce humic-like FDOM accumulation in seawater - Zhang, Lianbao; Liu, Yeping; Chen, Li; Song, Hui (Frontiers in Marine Science, 2023)
Climate change can increase riverine discharge, which will promote terrigenous particle transportation and deeply impact microbe-mediated biogeochemical processes in the estuarine ecosystem. However, little is known about the long-term impacts of terrigenous particles on autotrophic and heterotrophic microbial community structures due to in situ continuous particle input. To solve this problem, a large-volume indoor incubation experiment was set up for over 40 days to simulate terrigenous particle input scenario. The activity and community structures of keystone groups were largely correlated with biochemical components derived from the terrigenous particles. The ecosystem was maintained by chemoautotrophic nitrifiers before the addition of terrigenous particles. The system was then functionally dominated by heterotrophic microorganisms after the input of terrigenous particles because terrigenous particles created environments that allowed heterotrophs to proliferate better than chemoautotrophs. The input of terrigenous particles increased the relative intensity of humic-like compounds mainly through releasing nutrients and biological labile organic matter to the seawater, which promoted the microbial transformation of organic matter. This study illustrates that terrigenous particles can impact the balance between heterotrophic and chemoautotrophic microbes and play an important role in humic-like compound transformation in seawater.